Pelatihan Rebranding Produk Untuk Perluasan Pasar Sangkar Burung Di Kabupaten Jember - Mukhamad Zulianto; Bejo Apriyanto (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2022)
Abstract: Brands in SMEs consist of a set of factors, including marketability and market differentiation, brand awareness, relevance, culture, association, and equity. The most important thing to ask yourself when deciding whether this is the right time to change your brand is whether SMEs can leverage any of the factors above to make SME consumers happier. Rebranding is an excellent way to change the target market for SMEs. Sees rebranding as a solution to a new management change or internal problem. Rebranding takes time and effort so that change will happen. Rebranding is carried out for SMEs to stimulate growth, expand, increase profits, strengthen their workforce, and gain a competitive advantage. This rebranding training was carried out using a training method. Due to the pandemic, the activity organizers visited five artisans to avoid crowds. The rebranding training opened the insight of the craftsmen about the benefits of managing a product brand. The rebranding training for birdcage artisans in Dawuhanmangli Village gained an understanding of branding. As a result of this training, artisans began to open themselves to introduce their products directly to consumers without a broker like before. The Bird Cage craft center in Dawuhanmangli Village, north of the center of Jember City, is well known in Indonesia. The location is 24 km from Jember City. The Bird Cage of Dawuhanmangli Village is the reason for being a place of service because it has advantages and characteristics that have the opportunity to open new markets for the region's superior products.         Keywords: branding; smes; bird cageAbstrak: Merek pada UMKM terdiri dari sekumpulan faktor, termasuk kemampuan pemasaran serta diferensiasi pasar, kesadaran merek, relevansi, budaya, asosiasi, dan ekuitas. Hal terpenting untuk ditanyakan pada diri sendiri saat memutuskan apakah ini waktu yang tepat untuk mengubah merek adalah apakah UMKM dapat meningkatkan salah satu faktor di atas untuk membuat konsumen UMKM lebih bahagia. Rebranding merupakan cara yang baik untuk mengubah target pasar UMKM. Melihat rebranding sebagai solusi untuk perubahan manajemen baru atau masalah internal. Rebranding membutuhkan waktu dan tenaga, sehingga perubahan akan terjadi. Rebranding dilakukan bagi UMKM untuk merangsang pertumbuhan, memperluas, meningkatkan laba, memperkuat tenaga kerjanya, dan mendapatkan keunggulan kompetitif. Pelatihan Rebranding ini dilakuan dengan metode pelatihan, dikarenakan pandemi, maka pelaksana kegiatan mendatangi 5 pengrajin untuk menghindari kerumuman. Pelatihan rebranding membuka wawasan para pengrajin tentang manfaat mengelola sebua brand sebuah produk. Hasil pelatihan rebranding pengrajin sangkar burung desa Dawuhan mangli mendapatkan pemahaman tentang branding. Dampak pelatihan ini pengrajin mulai mencoba membuka diri untuk mengenalkan produknya secara langsung kepada konsumen tanpa makelar seperti sebelumnya. Sentra kerajinan Sangkar Burung di desa Dawuhan mangli, wilayah utara pusat Kota Jember sudah dikenal luas di Indonesia.Kata kunci: merek; umkm; sangkar burung